Determining the Source Parameters of the Jambi Earthquake (1 October 2009, Mw=6.4) Using Three-Component Local Waveforms - Madlazim, Madlazim (Makara Journal of Science, 2013)
The purpose of this research was to estimate the source parameters of a mainshock earthquake (Mw=6.4) that occurred on 1 October 2009 in the Dikit major segment of the Sumatran Fault Zone (SFZ). The source parameters were analyzed by the inversion of three-component local waveforms recorded by the GEOFON broadband IA network. Moment tensor of the event was determined using the Discrete Wave number method to calculate the Green function and the iterative deconvolution method to invert the moment tensors. From the analysis, we obtained the fault parameters of the mainshock, which are strike=324°, dip= 80° and rake= -173°. Abstra